Basic liver immunology - Gao, Bin (Cellular & molecular immunology, 2016)
The liver is the largest solid organ in the body and has many unique immunological properties, including induction of immune tolerance, strong innate immunity, poor adaptive immune response versus overreactive autoimmunity and hematopoiesis in the fetal liver. Thus, the liver has been proposed as ＇an immunological organ＇. Although the primary functions of the liver are not traditionally considered to be immunological, the liver also performs many essential immune tasks. For example, hepatocytes are responsible for the production of 80-90% of the circulating innate immunity proteins in the body,